2005
DOI: 10.1038/ni1222
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal function for cytoplasmic protein FROUNT in CCR2-mediated monocyte chemotaxis

Abstract: Ligation of the chemokine receptor CCR2 on monocytes and macrophages with its ligand CCL2 results in activation of the cascade consisting of phosphatidylinositol-3-OH kinase (PI(3)K), the small G protein Rac and lamellipodium protrusion. We show here that a unique clathrin heavy-chain repeat homology protein, FROUNT, directly bound activated CCR2 and formed clusters at the cell front during chemotaxis. Overexpression of FROUNT amplified the chemokine-elicited PI(3)K-Rac-lamellipodium protrusion cascade and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 40 publications
5
119
0
Order By: Relevance
“…In this study, we confirmed that CCR2-Jurkat migrate dose-dependently toward recombinant mouse MCP-1; 100 nM was most effective to induce chemotaxis ( Fig. S2), which is consistent with a previous report (25). Thus, 100 nM recombinant MCP-1 was used for further analysis.…”
Section: Methodssupporting
confidence: 76%
“…In this study, we confirmed that CCR2-Jurkat migrate dose-dependently toward recombinant mouse MCP-1; 100 nM was most effective to induce chemotaxis ( Fig. S2), which is consistent with a previous report (25). Thus, 100 nM recombinant MCP-1 was used for further analysis.…”
Section: Methodssupporting
confidence: 76%
“…Candidate proteins from the high stringency threshold include HERC4, a probable E3 ubiquitin-protein ligase by sequence similarity (Wu et al 2006), and NUP85, a component of the nuclear pore complex thought to play a role in phosphatidyl-inositol-3-kinase-dependent pathways (Terashima et al 2005). CAPNS1, scoring 4.0 (rank 7; moderate), belongs to a well-conserved family of calcium-dependent, cysteine proteases whose link to cellular senescence and DNA damage response has been studied (Demarchi and Schneider 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of Akt membrane recruitment in these studies was highly variable. Furthermore, none of these studies appear to have compared the activity and/or function of these constructs to the endogenous protein (Asano et al, 2008;Calleja et al, 2003;Carpten et al, 2007;Cenni et al, 2003;Currie et al, 1999;Du et al, 2014;Feng et al, 2014;Gonzalez and McGraw, 2009;Huang et al, 2011;Imazaki et al, 2010;Kontos et al, 1998;Lasserre et al, 2008;Parikh et al, 2012;Rodríguez-Escudero et al, 2005;Servant et al, 2000;Terashima et al, 2005;Watton and Downward, 1999;Zhang et al, 2009). While GFP remains the most commonly used fluorescent protein, there are a growing number of publications that report fusion protein dysfunction (Goto et al, 2003;Huang and Shusta, 2006;Kalatskaya et al, 2006;Liu et al, 1999;Yantsevich et al, 2009) and mislocalisation (Skube et al, 2010;Zhu et al, 2013), which one group has attributed to the affinity of eGFP for the nucleus (Seibel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%